Long-term intermittent low-frequency repetitive transcranial magnetic stimulation effectively controls seizures in two drug-free adolescent patients - Li, Hongzhan; Wang, Chunyan; Zhang, Shaotian; Zhang, Chengliang; Lu, Rulan; Yun, Wenwei; Zhou, Xianju (Journal of international medical research, 2019)
Recently, repetitive transcranial magnetic stimulation (rTMS) has been widely used for treating neurological and psychiatric diseases. Low-frequency rTMS is used to effectively control the occurrence of seizures, including medication-refractory epilepsy and cortical dysplasia or neocortical epilepsy. However, there have been no reports on the effects of long-term rTMS on epilepsy. We observed the clinical effects of long-term rTMS in two drug-free adolescent epileptic patients with a preference for non-drug therapy. The two drug-free adolescent patients, who underwent intermittent low-frequency rTMS treatment for 36 weeks, obtained effective control of seizures (including episode and severity). However, a systematic study is required to confirm our observations.